2016
DOI: 10.56431/p-qs8am2
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variability of Carbon Monoxide (CO) in the Ambient Environment of IMO State, Nigeria

Abstract: The air quality of four areas in Imo State with a total of twenty two locations was monitored for a period six months with respect to CO level using Gasman air monitor (Crowcon Instruments Ltd, England. The air quality monitoring was conducted in the morning, afternoon and evening hours within dry and wet seasons in order to elucidate the variability of this atmospheric pollutant in the study locations. The results obtained showed significant variation of the air pollutant in the morning, afternoon and evening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The variation in atmospheric temperature in this study is suggested to be due to differences in the time of the day that the reading was made(Ubuoh et al, 2022). The temperature of the study is consistent with the reports of the ambient temperature obtained byGobo et al (2012) in Rivers State,Njoku et al (2016) in Lagos state, Antai et al (2016) in Akwa Ibom State, and Ubuoh et al(2022) in Imo State, 27.5-30.17 o C in Lafarge cement in Ogun State (Soyebo and Kehinde, 2020). The mean values of temperature of the study were below the daily temperature limit of 36 o C (WHO, 2005).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The variation in atmospheric temperature in this study is suggested to be due to differences in the time of the day that the reading was made(Ubuoh et al, 2022). The temperature of the study is consistent with the reports of the ambient temperature obtained byGobo et al (2012) in Rivers State,Njoku et al (2016) in Lagos state, Antai et al (2016) in Akwa Ibom State, and Ubuoh et al(2022) in Imo State, 27.5-30.17 o C in Lafarge cement in Ogun State (Soyebo and Kehinde, 2020). The mean values of temperature of the study were below the daily temperature limit of 36 o C (WHO, 2005).…”
supporting
confidence: 90%
“…The result of NO2 of the study at the three locations were all above the 0.02 ppm (WHO), 0.04-0.06ppm (FMEnv/NAAQS) permissible limit for clean air. High concentration of Oxides of Nitrogen (NOx) can trigger respiratory ailments, lung diseases as well as susceptibility to respiratory infection (Njoku et al, 2016). This NOx is capable of causing high levels of tropospheric ozone, suspended particle and methane which is a greenhouse gas (USEPA, 2007).…”
Section: Temporal Dynamics Of Dry Atmospheric Chemistry In Cement Mil...mentioning
confidence: 99%
See 1 more Smart Citation